MENGEMBALIKAN MISI PENDIDIKAN SOSIAL DAN KEBUDAYAAN PESANTREN - Naim, Ngainun (Jurnal Pendidikan Islam, 2016)
This paper intends to reposition Islamic boarding school (Pesantren) as an educational institution that is likely to contribute greatly to the formation of Indonesian identity in the future. The discussion involves the analysis of philosophy, history, sociology, anthropology, theology and education. Data were collected textually and contextually. The result shows that Pesantren is the first educational institution (the 13th Century) that focuses on forming values, moral and socio-cultural character of Indonesia. Some of the orders were passed on in the form of Indonesian Islamic law, architecture and puppets. There are three basic characters that allow schools (Pesantren) to carry out this mission: 1) institutional system that is integrated with the community, 2) intensive ongoing learning system (pondok) and 3) implementation of principles that are based on the universal teachings of Islam can be interpreted in three dimensions, the mythic and the ontological functional (Van Peursen, 1998). Strategically, all three can return the mission of the schools (Pesantren): build and develop the character, moral (akhlak), social (ummat), culture (adab) and religiosity of Indonesia.